NON- PENERAPAN MODEL PEMBELAJARAN TGT (TEAMS GAMES TOURNAMENT) DENGAN PERMAINAN COC (CLASS OF CHAMPIONS) TERHADAP HASIL BELAJAR SISWA: BAHASA INDONESIA - MUHIBBATUD DIANA RIDHO; Kusmiati Kusmiati (Jurnal Cendekia Pendidikan, 2024)
The Teams Games Tournament (TGT) learning model is a learning approach where students learn in groups. TGT is very easy to implement among students, as this model emphasizes the activity and cooperation of all students. This model can engage all students' activities by incorporating elements of play. This TGT model is suitable for the subject of Mathematics. In learning that uses this model, students are expected to be able to construct and organize their own knowledge. There are five steps in implementing the TGT learning model: 1) Delivering information, 2) Team formation, 3) Games, 4) Tournaments, and 5) Group awards. With the Class Of Champions (COC) game, in addition to testing academic abilities, COC also serves as a platform to instill important values such as teamwork, courage in facing challenges, and discipline. By using gaming applications (Wordwall, quizizz, dll) in digital technology, simple games can be utilized to encourage students to develop correct thinking, proper speaking, and appropriate actions. Thus, the learning process using the TGT model with the Class Of Champions game can improve students' learning outcomes.